APPLICATION OF ADSORPTION PHYSICS FOR HANDLING ENVIRONMENTAL POLLUTION- ONE METHOD OF DECONTAMINATION OF RADIOACTIVE SEAWATER- - Eiji Ishizaki, Atsushi Minato, Masanori Itaba & Satoru Ozawa (International Journal of Research Science and Management, 2015)
In recent years, nuclear power plants are going to be introduced to developing countries to cover their increasing needs of electric power supply. In case of nuclear power plant accident, various top-level scientific and engineering techniques are needed to manage the accident. One of them is removal technique of radioactive materials from polluted soils or water. This paper reports the lessons learnt from the Fukushima nuclear power accident in 2011. One method is presented of the radioactive decontamination of the seawater polluted by the accident of Fukushima nuclear plant 1. The point is how to decontaminate huge amount of the polluted seawater in the harbor where the radioactive materials are accumulated especially in the neighborhood of the nuclear power plants. It has been shown a molecular sieve zeolite (MSZ) in a pillar buoy that floats in the harbor effectively collects 90Sr from the polluted seawater.